Quality of Life and Physical Exercise Overview in Congestive Heart Failure Patients Using Six-Minute Walk Test - Bestalia, Nova; Dewi, Wan Nashifa; Karim, Darwin (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
Efforts to improve the quality of life for patients with congestive heart failure can be made through the Six Minute Walk Test (6MWT) physical exercise. This study explores the role of 6MWT, which is not only used as an assessment tool but also as a structured exercise intervention that can help improve the quality of life of heart failure patients. The aim of this study is to determine the impact of 6MWT physical exercise on the quality of life of patients with congestive heart failure. The study design used is quantitative with a descriptive approach, involving 36 respondents selected using purposive sampling technique. The variables studied include 6MWT physical exercise measured by the Standard Operating Procedure (SOP) implemented at RS Arifin Achmad in Riau Province, and the quality of life of patients measured using the Minnesota Living with Heart Failure Questionnaire (MLHFQ). The results showed that the majority of respondents were in the pre-elderly age group (52.8%), male (63.9%), had a high school education (44.4%), and most were unemployed (41.7%). All patients underwent 6MWT physical exercise according to the SOP (100%). The quality of life of the patients was mostly categorized as moderate (86.1%) and poor (13.9%). Based on these findings, it can be concluded that the application of 6MWT physical exercise according to SOP has the potential to improve the quality of life of patients with congestive heart failure.